2014
DOI: 10.1037/a0034547
|View full text |Cite
|
Sign up to set email alerts
|

Best practices for remote psychological assessment via telehealth technologies.

Abstract: The use and capabilities of telehealth technologies to conduct psychological assessments remotely are expanding. Clinical practitioners and researchers need to be aware of what influences the psychometric properties of telehealth-based assessments to assure optimal and competent assessments. The purpose of this review is to discuss the specific factors that influence the validity and reliability of remote psychological assessments and to provide best practices recommendations. Specific factors discussed includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
132
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(140 citation statements)
references
References 83 publications
0
132
0
8
Order By: Relevance
“…Online communication is the single mode of therapeutic intervention, substituting for traditional face-to-face practice. With clear protocols, therapeutic interventions are conducted through designated software (e.g., asynchronous email, synchronous chat) with security protections using computers (Chester and Glass 2006;Luxton et al 2014;Hollis et al 2015) and/or mobile applications and messaging services (Epstein and Bequette 2013;Prentice and Dobson 2014;Whittaker et al 2012). Formal Online ICTs may also consist of video counseling or virtual world communication.…”
Section: Ict Use In Clinical Practicementioning
confidence: 99%
“…Online communication is the single mode of therapeutic intervention, substituting for traditional face-to-face practice. With clear protocols, therapeutic interventions are conducted through designated software (e.g., asynchronous email, synchronous chat) with security protections using computers (Chester and Glass 2006;Luxton et al 2014;Hollis et al 2015) and/or mobile applications and messaging services (Epstein and Bequette 2013;Prentice and Dobson 2014;Whittaker et al 2012). Formal Online ICTs may also consist of video counseling or virtual world communication.…”
Section: Ict Use In Clinical Practicementioning
confidence: 99%
“…Prior studies have successfully collected both assessment data via distance (Luxton, Pruitt, & Osenbach, 2014) and implemented language interventions via distance (McDuffie et al, 2013; McDuffie, Machalicek, et al, 2016; McDuffie, Oakes, et al, 2016; Oakes, Ma, McDuffie, Machalicek, & Abbeduto, 2015). McDuffie et al (2013) found that targeted parent behaviors were used as frequently during video-conferencing sessions as they were during face-to-face sessions conducted in the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we have not yet demonstrated reliability and validity of the remote assessment, though we also recognize this is challenging with rare diseases where sample size, and sampling opportunities, are limited. We are encouraged by prior studies that have established the psychometric properties of remote psychological evaluations, including cognitive assessment 38 …”
Section: Discussionmentioning
confidence: 99%